(untitled) (Research, Society and Development, 2023)
Risk perception can be considered a very significant determinant of people’s behavior change. This study aims to study the perception of risk and knowledge in hygiene by customers of small and medium-sized supermarkets in cities in the region of Recôncavo Baiano, BA. The research was carried out with 300 people over 18 years of age, with a level of education ranging from incomplete elementary education to complete higher education. A structured questionnaire was applied to assess sociodemographic information, perceptions of risk in relation to the practices carried out and knowledge of hygiene. The questionnaire was applied via Google Forms, the target audience was approached via social networks and emails. Given the above, it is possible to conclude that through the questionnaire it was possible to observe that supermarket customers can have a perception of the risks that certain attitudes carried out by supermarkets may have, as well as being able to assess the hygiene conditions in which they find themselves.